PROFIL SPEKTRA INFRA MERAH SERBUK Gelidium Zollingeri DENGAN ANALISIS PCA - Farizah Izazi; Yuyun Nailufa (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2022)
Gellidium zolingeri is a red alga of the Rhodophyta. Content of Gellidium zolingeri is Mycosporine-like amino acids (MAAs), proteins (amino acids), pigments (phycobiliproteins and carotenoids), phenolic compounds, fucoidan etc. Gellidium zolingeri has several benefits. From the drug content, Gellidium zolingeri can be used as a natural product. Different content in a plant is influenced by several factors, one of which is the climate and harvest time. It is known that in this study using three different harvest times, different harvest times will affect the percentage or content of the plant. Therefore, to ensure its quality, this research is carried out. Result analysis using Infrared Spectrophotometry, five functional groups were obtained, OH carboxylic acid, N-H (cyclic alkene), C=C (aromatic), C-O (ether) and =C-H (alkene) with their respective wave numbers. Result from spectra that these compounds are MAAs. Next step analyzed by PCA (Principal Component Analysis) minitab19, the data obtained are Score plots, Loading plots and Biplots. The results of the three samples with different collection times have three different spectra results. Harvest time of November the dry season and harvest time of December and January the rainy season is grouped separately. November is also a transitional climate where results of these spectra are in between the rainy season spectra (December and January).